TRADISI LARANGAN NIKAH SESUKU DI DESA PARITBARU DITINJAU DARI PERSPEKTIF HUKUM ISLAM (AL-QUR`AN DAN HADIS) - ABROR, MHD. (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
Marriage is something sacred in one's life, almost all humans desire marriage. In the Big Indonesian Dictionary it is stated that marriage is an agreement between a man and a woman to legally become husband and wife. But sometimes, the hope of having a household to become a sakinah mawaddah wa rahmah family fails before the marriage contract is caused by many factors, both in terms of family, heredity and even tradition. The results of the research show that same-ethnic marriage has occurred in Paritbaru Village, which was actually prohibited by the traditional stakeholders in the village. When someone wants to get married, the first thing that is seen or asked is the tribe of the future wife or husband, if they come from the same tribe, there will be rejection, both from the family and especially from the grandmother or adat leaders in the village, for example if the man -the man has a Malay ethnicity and his future wife is also from a Malay ethnicity, so in Paritbaru Village their marriage will be prohibited by the adat leaders. This study uses a case study as a research approach to analyze the tradition of prohibiting same-sex marriage in Paritbaru Village, located in Kampar district, Riau, Indonesia from the perspective of the Qur'an and Hadith. The data collection method used is observation and direct interviews. In the observation stage of the researcher as participant-observation. Furthermore, data was also collected from in-depth semi-structured interviews with same-ethnic marriage actors, ninik mamak (traditional leaders) and local religious leaders. At first, the ban on same-ethnic marriages started because there was a concern that they would also be breastfed, because in the past the people of Paritbaru Village lived in groups according to their respective tribes, they lived in the house